A new flow cell and chemometric protocol for implementing in‐line Raman spectroscopy in chromatography. (28th May 2019) - Feidl, Fabian; Garbellini, Simone; Vogg, Sebastian; Sokolov, Michael; Souquet, Jonathan; Broly, Hervé; Butté, Alessandro; Morbidelli, Massimo
Abstract: On‐line monitoring tools for downstream chromatographic processing (DSP) of biotherapeutics can enable fast actions to correct for disturbances in the upstream, gain process understanding, and eventually lead to process optimization. While UV/Vis spectroscopy is mostly assessing the protein's amino acid composition and the application of Fourier transform infrared spectroscopy is limited due to strong water interactions, Raman spectroscopy is able to assess the secondary and tertiary protein structure without significant water interactions. The aim of this work is to implement the Raman technology in DSP, by designing an in‐line flow cell with a reduced dead volume of 80 μL and a reflector to increase the signal intensity as well as developing a chemometric modeling path. In this context, measurement settings were adjusted and spectra were taken from different chromatographic breakthrough curves of IgG1 in harvest. The resulting models show a small average RMSEP of 0.12 mg/mL, on a broad calibration range from 0 to 2.82 mg/mL IgG1. This work highlights the benefits of model assisted Raman spectroscopy in chromatography with complex backgrounds, lays the fundamentals for in‐line monitoring of IgG1, and enables advanced control strategies. Moreover, the approach might be extended to further critical quality attributes like aggregates or could be transferred to other process steps.